Abraham Joshua Heschel The Call of Transcendence. - Held, Shai. (Bloomington : Indiana University Press, 2013)
Abraham Joshua Heschel (1907-1972) was a prolific scholar, impassioned theologian, and prominent activist who participated in the black civil rights movement and the campaign against the Vietnam War. He has been hailed as a hero, honored as a visionary, and endlessly quoted as a devotional writer. In this sympathetic, yet critical, examination, Shai Held elicits the overarching themes and unity of Heschel's incisive and insightful thought. Focusing on the idea of transcendence-or the movement from self-centeredness to God-centeredness-Held puts Heschel into dialogue with contemporary Jewish.
No; p; r; s; t; u; v; w; z
Description based upon print version of record.
Keywords: Heschel, Abraham Joshua, 1907-1972.; Jewish scholars -- United States -- Biography; Judaism -- Doctrines; Heschel Abraham Joshua--1907-1972--Teachings.; Judaism -- Doctrines; God (Judaism); Electronic books.--local; RELIGION / Judaism / General; Electronic books